若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 14:19:54
若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=若(x平方-3xy+y+x-5)平方
若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=
若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=
若(x平方-3xy+y+x-5)平方+|3x+1|=0,则x平方-3xy+y-2=
(x平方-3xy+y+x-5)平方+|3x+1|=0
则
(x平方-3xy+y+x-5)平方=0,|3x+1|=0
x²-3xy+y+x-5=0
3x+1=0
x=-1/3
所以
x²-3xy+y-2+x-5+2=0
x²-3xy+y-2=3-x=3+1/3=10/3
∵(x平方-3xy+y+x-5)平方+|3x+1|=0
∴3x+1=0 x=-1/3
x²-3xy+y+x-5=0
x ²-3xy+y-2=3-(-1/3)=3+1/3=3又1/3
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
初一2x平方-5xy-3x平方+4y平方+3xy-y平方
5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
计算:(x平方+y平方/xy-x平方/xy+y平方-y平方/x平方+xy)除以3/xy
2x平方y-2xy+3xy平方+5+2xy+x平方y-3xy平方-3 过程!
(3X平方-5Y)+[-3XY-2(X平方-XY)+Y平方]
x平方-5xy+6y平方
5x平方-(3y平方+5x平方)+(4y平方+3xy)化筒
5x平方y+3x平方y平方—4xy平方=?
5xy平方-2x平方y+[3xy平方-(4xy-2x平方y-2x平方y)],其中x=-2,y=-1求值
计算 5xy的平方-【3xy的平方-(4xy的平方-2x的平方y)】+2x的平方y-xy的平方
4X的平方-3XY-( )等于5X平方+4XY-Y平方
先化简后求值 (5x的平方-3y的平方)-[(5x平方-3xy-y平方)-(x平方-3xy+3y平方)] 其中x=3
若5(3x的平方y-xy的平方)-(xy的平方+3x的平方y)其中x=二分之一y=三分之一
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
[x(x平方y平方-xy)-y(x平方-x3立方)]÷3x平方y
化简3x平方-5xy+3y平方
2x平方-5xy-3y平方 因式分解